Positive electrode active material and preparation method and application thereof
By coating the phosphate material with NASICON structure with lithium transition metal oxide, the problems of limited energy and poor structural stability of the existing power lithium battery positive electrode material are solved, and higher cycle and first-circuit Coulomb efficiency performance are achieved, improving The structural stability and safety of the battery.
Patent Information
- Application Number
- CN202310957391.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
The specific energy of the existing power lithium battery positive electrode material is limited, which is difficult to meet the requirements of new energy vehicles for high range. At the same time, the structural phase change of high-nickel materials during charging and discharging leads to a decrease in material stability, and the side reaction with the electrolyte results in Battery capacity attenuation and safety issues.
The lithium transition metal oxide is coated with a phosphate material with a sodium fast ion conductor (NASICON) structure, and the diffusion rate of lithium ions and the structural stability of the material are improved by wet coating.
It significantly improves the circulation and first-circle Coulomb efficiency performance of lithium transition metal oxide positive electrode material, improves the structural stability of the material and lithium ion transmission dynamics, and slows down battery capacity attenuation and safety issues.
Smart Images

Figure CN119447204A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium battery materials, and in particular to a positive electrode active material and a preparation method and application thereof. Background Art
[0002] Rechargeable lithium-ion secondary batteries have been widely used in modern communications, portable electronic products and hybrid vehicles due to their advantages such as high specific energy, long charge and discharge life, no memory effect, low self-discharge rate, fast charging, no pollution, wide operating temperature range and safety and reliability. Especially in recent years, with the continuous development of the new energy vehicle industry, higher requirements have been put forward for power lithium-ion secondary batteries. Studies have shown that positive electrode materials are currently the key factor limiting the improvement of power lithium battery performance. At present, the commercial power battery positive electrode materials are mainly lithium cobalt oxide and lithium iron phosphate, but their specific energy is limited and it is difficult to meet the requirements of future new energy vehicles for high mileage.
[0003] The high nickel cathode material of lithium-ion batteries exhibits high specific capacity and energy density, and is considered to be the next generation of large-scale power battery cathode materials. However, during the charging and discharging process, the structural phase change of the high nickel material causes the material anisotropy to change, and the stress generated causes particle pulverization and microcracks, which significantly reduces the material stability. At the same time, the electrolyte will penetrate into the surface and microcracks, triggering side reactions between the electrode and the electrolyte, causing battery capacity decay and a series of safety issues. In addition, at the solid-liquid interface between the electrode and the electrolyte, the impedance of lithium ion transmission is very large, which will further reduce the battery capacity and rate performance. Ion conductor coating can significantly reduce the side reactions between the electrolyte and the battery material, while maintaining the structural stability of the battery material, alleviating the structural strain caused by material stress, and regulating lithium ion interface transmission. Summary of the invention
[0004] In response to the problems existing in the prior art, the present disclosure aims to improve the circulation and first-cycle coulombic efficiency performance of lithium transition metal oxide by coating a phosphate material with a sodium fast ion conductor (NASICON) structure with a lithium transition metal oxide.
[0005] The present disclosure provides a positive electrode active material, the positive electrode active material comprising a lithium transition metal oxide having the following chemical formula 1 and a coating layer coated on the surface of the lithium transition metal oxide;
[0006] Chemical formula 1: LiNi a Co b Mn c M 1 d O 2; where a+b+c+d=1, 0.80≤a≤1, 0≤b≤0.20, 0≤c≤0.20, 0≤d≤0.10, M 1 At least one selected from Al, B, Sr, Y, Ba, W, Ca, Cu, Fe, V, Cr, Ti, Zr, Zn, In, Ta, La, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo; the coating layer comprises a phosphate material, the phosphate material having M 0.5 Zr 2 (PO 4 ) 3 The chemical formula of , M is selected from at least one of Mg, Ca, Ni, and Mn.
[0007] The present disclosure provides a positive electrode active material, the positive electrode active material comprising a lithium transition metal oxide having the following chemical formula 2 and a coating layer coated on the surface of the lithium transition metal oxide;
[0008] Chemical formula 2: LiNi a Co b Mn c O 2 ; wherein a+b+c=1, 0.80≤a<1, 0<b≤0.20, 0<c≤0.20; the coating layer comprises a phosphate material, the phosphate material has M 0.5 Zr 2 (PO 4 ) 3 The chemical formula of , M is selected from at least one of Mg, Ca, Ni, and Mn.
[0009] In one aspect of the present disclosure, the phosphate material has a sodium fast ion conductor (NASICON) structure.
[0010] In one aspect of the present disclosure, the coating layer has a thickness of 2-10 nm.
[0011] In one aspect of the present disclosure, the cathode active material includes primary particles having a Dv50 of 2-5 μm.
[0012] In another aspect of the present disclosure, the positive active material includes secondary particles having a Dv50 of 10-14 μm.
[0013] In one aspect of the present disclosure, based on the total mass of the positive electrode active material, the mass percentage of the phosphate material is 0.3-1.2%.
[0014] In one aspect of the present disclosure, the phosphate material is selected from Mg 0.5 Zr 2 (PO 4) 3 and / or Ca 0.5 Zr 2 (PO 4 ) 3 .
[0015] In one aspect of the present disclosure, the phosphate material has a thickness of 2-10 nm, for example, the phosphate material has a thickness of 5 nm.
[0016] In one aspect of the present disclosure, the lithium transition metal oxide is
[0017] LiNi 0.92 Co 0.04 Mn 0.04 O 2 .
[0018] In one aspect of the present disclosure, the zirconium salt is selected from zirconium nitrate.
[0019] The present disclosure provides a method for preparing the aforementioned positive electrode active material, the method comprising the following steps:
[0020] Dissolving the lithium transition metal oxide, zirconium salt, phosphoric acid and metal salt of M in a solvent;
[0021] Stirring for 2-6 hours, and drying to obtain a mixture;
[0022] The mixture is subjected to a heating treatment to obtain a positive electrode active material.
[0023] In one aspect of the present disclosure, the molar ratio of the lithium transition metal oxide, zirconium salt, phosphoric acid and metal salt of M is selected from (1): (0.002-0.01): (0.002-0.015): (0.001-0.005).
[0024] In one aspect of the present disclosure, the metal salt of M is selected from at least one of magnesium nitrate, calcium nitrate, nickel nitrate and manganese nitrate.
[0025] In one aspect of the disclosure, the solvent is ethanol.
[0026] In one aspect of the present disclosure, the heat treatment is performed under an oxygen atmosphere.
[0027] In one aspect of the present disclosure, the temperature of the heat treatment is selected from 500°C-700°C.
[0028] In the present disclosure, the method for preparing a positive electrode active material further includes steps 1-1 to 1-3 of preparing a precursor:
[0029] 1-1: Dissolve nickel salt, cobalt salt and manganese salt in water to obtain solution A;
[0030] 1-2: adding the solution A to the alkaline solution while stirring at 50-70° C., adjusting the pH value to 9.5, and continuing stirring for 3-6 hours to obtain solution B;
[0031] 1-3: Purify the solution B to obtain a precursor.
[0032] In one aspect of the present disclosure, the precursor is Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 .
[0033] In one aspect of the present disclosure, the molar ratio of the nickel salt, cobalt salt and manganese salt is selected from (90-96):(1-5):(1-5); for example, the molar ratio of the nickel salt, cobalt salt and manganese salt can be 92:4:4.
[0034] In one aspect of the present disclosure, the nickel salt, cobalt salt and manganese salt are nickel sulfate, cobalt sulfate and manganese sulfate; or, the nickel salt, cobalt salt and manganese salt are nickel nitrate, cobalt nitrate and manganese nitrate.
[0035] In one aspect of the present disclosure, in step 1-1, in the solution A, the total metal molar concentration is selected from 1.0-3.0 mol / L; preferably 1.5-2.5 mol / L; more preferably 2 mol / L.
[0036] In one aspect of the present disclosure, in step 1-2, the alkaline solution is a mixed solution of aqueous ammonia and NaOH solution, the concentration of aqueous ammonia is selected from 0.8-1.5 mol / L, preferably 0.9 mol / L or 1.2 mol / L; the concentration of NaOH is selected from 0.8-2.2 mol / L, preferably 1.0 mol / L or 2.0 mol / L.
[0037] In one aspect of the present disclosure, in steps 1-3, the purification treatment includes washing, filtration and drying processes.
[0038] In the present disclosure, the method for preparing a positive electrode active material further includes steps 2-1 to 2-2 of preparing a lithium transition metal oxide using a precursor:
[0039] 2-1: mixing the precursor and the lithium-containing compound to obtain a mixture 2;
[0040] 2-2: The mixture 2 is calcined to obtain a lithium transition metal oxide.
[0041] In one aspect of the present disclosure, in step 2-1, the lithium-containing compound is lithium hydroxide.
[0042] In one aspect of the present disclosure, in step 2-1, the molar ratio of the precursor to the lithium-containing compound is selected from (1): (1.02-1.08).
[0043] In one aspect of the present disclosure, in step 2-2, the calcination treatment is performed under an oxygen atmosphere.
[0044] In one aspect of the present disclosure, in step 2-2, the calcination treatment is: calcination at 450°C-500°C for 2-4 hours, and then calcination at 720°C-780°C for 10-14 hours.
[0045] In one aspect of the present disclosure, in step 2-2, after the calcination treatment, ball milling and a second calcination treatment may be further included to obtain a lithium transition metal oxide having a single crystal structure; the second calcination treatment is calcined at 600°C-800°C for 6-10 hours.
[0046] The present disclosure also provides an electrochemical device, which includes the above-mentioned positive electrode active material.
[0047] The present disclosure also provides an electrical device, which includes the aforementioned electrochemical device.
[0048] Beneficial effects:
[0049] Compared with the metal phosphate (MPO) produced by pyrophosphate coating in the prior art 4 ) and lithium phosphate (Li 3 PO 4 ), the present invention adopts a wet coating method to coat a phosphate material M having a sodium fast ion conductor (NASICON) structure with higher ionic conductivity 0.5 Zr 2 (PO 4 ) 3 Coated lithium transition metal oxide polycrystalline materials and / or lithium transition metal oxide single crystal materials. Since zirconium-based phosphate materials have stable structures and are easy to synthesize, compared with single Zr phosphate coating, the introduction of M mainly increases ionic conductivity and serves as a structural skeleton to enhance stability. As a coating material, it can significantly inhibit the side reaction between the electrolyte and the lithium transition metal oxide positive electrode material, increase the diffusion rate of lithium ions, and significantly improve the structural stability of the lithium transition metal oxide positive electrode material and the slow lithium ion transfer kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1The preparation process of the positive electrode active material in Example 1 is shown;
[0051] Figure 2 The XRD pattern of the positive electrode active material obtained in Example 1 is shown;
[0052] Figure 3 The charge-discharge curve and the first-cycle coulombic efficiency of Example 3 are shown;
[0053] Figure 4 A TEM image of the positive electrode active material obtained in Example 3 is shown. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present disclosure. The embodiments of the present disclosure should not be interpreted as limiting the present disclosure.
[0055] the term:
[0056] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0057] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0058] In this document, it is necessary to understand that the orientations or positional relationships indicated by terms such as “upper”, “lower”, “top”, “bottom”, “inside” and “outside” are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0059] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0060] Unless otherwise specified, the terms used in this disclosure have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this disclosure).
[0061] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values explicitly designated as range limits, but also all individual numerical values or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.
[0062] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0063] In this article, the term "NASICON structure" refers to a 6 Octahedron and AO 4 The tetrahedron vertices are connected to form a three-dimensional open skeleton structure. In the NASICON structure, lithium ions are conducted in the channels formed by the gaps in the three-dimensional open skeleton structure, and the migration number is 1, so it has a high ionic conductivity.
[0064] In this article, "primary particles" refer to crystals within a few μm scale that do not contain grain boundaries, and the crystallographic orientation of the crystals remains basically consistent throughout the crystals; "secondary particles" refer to a collection of primary particles of many oriented grains, and the interior of the secondary particles is based on a lattice-like periodic structure, but is isotropic.
[0065] The present disclosure is further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.
[0067] positive electrode:
[0068] In some embodiments of the present disclosure, the positive electrode includes a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material coated on the positive electrode current collector. In the present disclosure, the positive electrode active material includes a lithium transition metal oxide having the following chemical formula 1 and a coating layer coated on the surface of the lithium transition metal oxide;
[0069] Chemical formula 1: LiNi a Co b Mn c M 1 d O 2 ; where a+b+c+d=1, 0.80≤a≤1, 0≤b≤0.20, 0≤c≤0.20, 0≤d≤0.10, M 1 At least one selected from Al, B, Sr, Y, Ba, W, Ca, Cu, Fe, V, Cr, Ti, Zr, Zn, In, Ta, La, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo; the coating layer comprises a phosphate material, the phosphate material having M 0.5 Zr 2 (PO 4 ) 3 The chemical formula of , M is selected from at least one of Mg, Ca, Ni, and Mn.
[0070] In some embodiments of the present disclosure, the positive active material includes primary particles having a Dv50 of 2-5 μm.
[0071] In some embodiments of the present disclosure, the positive electrode active material includes secondary particles having a Dv50 of 10-14 μm.
[0072] In some embodiments of the present disclosure, the coating layer has a thickness of 2-10 nm, preferably, the coating layer has a thickness of 4-6 nm, for example, the coating layer has a thickness of 5 nm.
[0073] In some embodiments of the present disclosure, the phosphate material is selected from Mg 0.5 Zr2 (PO 4 ) 3 or Ca 0.5 Zr 2 (PO 4 ) 3 .
[0074] In some embodiments of the present disclosure, the lithium transition metal oxide is
[0075] LiNi 0.92 Co 0.04 Mn 0.04 O 2 .
[0076] In some embodiments of the present disclosure, based on the total mass of the positive electrode active material, the mass percentage of the phosphate material is selected from 0.3-1.2%.
[0077] In some embodiments of the present disclosure, the lithium transition metal oxide is prepared by the following steps:
[0078] 1-1: Dissolve nickel salt, cobalt salt and manganese salt in water to obtain solution A;
[0079] 1-2: adding the solution A to the alkaline solution while stirring at 50-70° C., adjusting the pH value to 9.5, and continuing stirring for 3-6 hours to obtain solution B;
[0080] 1-3: Purifying the solution B to obtain a precursor;
[0081] 2-1: mixing the precursor and the lithium-containing compound to obtain a mixture 2;
[0082] 2-2: The mixture 2 is calcined to obtain a lithium transition metal oxide.
[0083] In some embodiments of the present disclosure, the positive electrode active material is prepared by the following steps:
[0084] 3-1: dissolving lithium transition metal oxide, zirconium salt, phosphoric acid and metal salt of M in a solvent, stirring for 2-6 hours, and drying to obtain a mixture;
[0085] 3-2: The mixture is subjected to a heating treatment to obtain the composite material.
[0086] In some embodiments of the present disclosure, in step 2-2, after the calcination treatment, ball milling and a second calcination treatment may be further included to obtain a lithium transition metal oxide having a single crystal structure; the second calcination treatment is calcined at 600°C-800°C for 6-10 hours.
[0087] In some embodiments of the present disclosure, in the method for preparing the positive electrode active material, it satisfies at least one of the following conditions:
[0088] (i) the molar ratio of the lithium transition metal oxide, zirconium salt, phosphoric acid and metal salt is selected from (1): (0.002-0.01): (0.002-0.015): (0.001-0.005);
[0089] (ii) the metal salt of M is selected from at least one of magnesium nitrate, calcium nitrate, nickel nitrate and manganese nitrate;
[0090] (iii) the solvent is ethanol;
[0091] (iv) the heat treatment is carried out in an oxygen atmosphere;
[0092] (v) The temperature of the heating treatment is selected from 500°C to 700°C.
[0093] In some embodiments of the present disclosure, the positive electrode active material further includes a binder, and optionally also includes a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0094] In some embodiments of the present disclosure, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0095] negative electrode:
[0096] In some embodiments of the present disclosure, the lithium-ion battery provided by the present disclosure further includes a negative electrode, the negative electrode includes a negative electrode plate, the negative electrode plate includes a current collector and a negative electrode active material disposed on the current collector. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , one or more of Li-Al alloys.
[0097] In some embodiments of the present disclosure, the negative electrode active material may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0098] In some embodiments of the present disclosure, the negative electrode sheet of the present disclosure includes a negative electrode active material, a binder and a conductive agent.
[0099] In some embodiments of the present disclosure, the negative electrode active material of the present disclosure may also be selected from other materials that can electrochemically absorb and release metal ions such as lithium ions. Specifically, it can be selected from carbonaceous materials, silicon materials, alloy materials, lithium-containing metal oxide materials, etc. They can be used alone or in any combination of two or more.
[0100] In some embodiments of the present disclosure, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0101] Diaphragm:
[0102] In some embodiments of the present disclosure, the lithium ion battery and electrochemical device of the present disclosure are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present disclosure are not particularly limited, and it can be any technology disclosed in the prior art.
[0103] In some embodiments of the present disclosure, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0104] In some embodiments of the present disclosure, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure.
[0105] Electrolyte:
[0106] The lithium-ion battery and electrochemical device involved in the present disclosure also include an electrolyte, and the electrolyte can be the electrolyte used in the prior art in the art.
[0107] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0108] In some embodiments, the electrolyte may optionally include additives.
[0109] Lithium-ion battery:
[0110] In some embodiments of the present disclosure, the lithium-ion battery involved in the present disclosure includes the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.
[0111] In some embodiments of the present disclosure, the lithium ion battery involved in the present disclosure may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a pouch-type soft package.
[0112] In some embodiments of the present disclosure, the lithium ion battery involved in the present disclosure is a cylindrical battery.
[0113] In some embodiments, the present disclosure further provides a battery module. The battery module includes the above-mentioned lithium-ion battery. The battery module of the present disclosure uses the above-mentioned lithium-ion battery, and therefore has at least the same advantages as the lithium-ion battery. The number of lithium-ion batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0114] In some embodiments, the present disclosure further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0115] Device:
[0116] The present disclosure also provides a device, which includes at least one of the above-mentioned lithium-ion battery, battery module or battery pack.
[0117] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or battery module may be used.
[0118] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0119] The present disclosure is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.
[0120] Examples and Comparative Examples
[0121] Test method:
[0122] Discharge capacity test: The assembled CR2025 button cell was placed in the Blue Electric electrochemical test system for power-on verification. The test was performed at a constant current of 0.1C (1C = 220mA / g). The voltage test window was 2.5-4.3V. The button cell was first charged to 4.3V at 0.1C constant current and then discharged to 2.5V at 0.1C.
[0123] Capacity retention rate test: The test was conducted at a current of 0.1C (1C = 220mA / g), and the voltage test window was 2.5-4.3V. The button battery was first charged at a constant current of 0.1C to 4.3V, and then discharged at 0.1C to 2.5V to complete one cycle. The above procedure was repeated for 100 cycles to obtain the capacity cycle retention rate.
[0124] Test of the first cycle coulombic efficiency: The assembled CR2025 button cell was placed in the Blue Electric electrochemical test system for buttoning verification, and the test was conducted at a current of 0.1C (1C = 220mA / g), and the voltage test window was 2.5-4.3V. The button cell was first charged at a constant current of 0.1C to 4.3V, and then discharged at 0.1C to 2.5V. The first cycle coulombic efficiency can be obtained.
[0125] Example 1
[0126] Embodiment 1 comprises the following steps:
[0127] Preparation of positive electrode composite materials:
[0128] The positive electrode active material of Example 1 includes Mg 0.5 Zr 2 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The preparation process of the positive electrode composite material of Example 1 is as follows Figure 1 As shown, the specific preparation method is as follows: dissolving nickel, cobalt and manganese sulfates in deionized water, wherein the molar concentration of the total metal in the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at the same time under stirring at 60°C, wherein the ammonia concentration is 1.2 mol / L and the NaOH concentration is 1.0 mol / L; adjusting the pH value to 9.5, stirring is continued at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor; Mix the precursor and lithium hydroxide in a stoichiometric ratio of 1:1.02, then transfer to a tube furnace, pre-burn at 475°C for 3 hours in an oxygen atmosphere, and then calcine at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. Take 100g of lithium transition metal oxide, 0.70g of zirconium nitrate, 0.08g of magnesium nitrate, and 0.10g of phosphoric acid and dissolve them in an ethanol solution. After sufficient high-speed stirring for 3 hours, heat and dry at 60°C. After sufficient grinding, calcine at 600°C for 6 hours in an oxygen atmosphere to obtain a positive electrode composite material. The XRD image of the obtained positive electrode composite material is as follows Figure 2 As shown, the crystal form after coating is still a pure layered structure, and the coating process does not change the main phase structure.
[0129] Preparation of button cells:
[0130] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0131] Embodiment 2:
[0132] Embodiment 2 comprises the following steps:
[0133] Preparation of positive electrode composite materials:
[0134] The positive electrode active material of Example 2 includes Mg 0.5 Zr 2 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The preparation method of the polycrystalline composite material is as follows: dissolving sulfates of nickel, cobalt and manganese in deionized water, wherein the molar concentration of the total metal in the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at the same time under stirring at 60°C, wherein the concentration of ammonia water is 1.2 mol / L and the concentration of NaOH is 1.0 mol / L; adjusting the pH value to 9.5, stirring is continued at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor; Mix the precursor and lithium hydroxide in a stoichiometric ratio of 1:1.02, then transfer to a tube furnace, pre-burn at 475°C for 3 hours in an oxygen atmosphere, and then calcine at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. Take 100g of lithium transition metal oxide, 0.88g of zirconium nitrate, 0.09g of magnesium nitrate, and 0.12g of phosphoric acid and dissolve them in an ethanol solution. After sufficient high-speed stirring for 3 hours, heat and dry at 60°C. After sufficient grinding, calcine at 600°C for 6 hours in an oxygen atmosphere to obtain a positive electrode composite material. The TEM image of the obtained positive electrode composite material is shown as follows. Figure 4 shown.
[0135] Preparation of button cells:
[0136] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in a N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0137] Embodiment 3:
[0138] Embodiment 3 comprises the following steps:
[0139] Preparation of positive electrode composite materials:
[0140] The positive electrode active material of Example 3 includes Mg 0.5 Zr 2 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The preparation method of the polycrystalline composite material is as follows: dissolving sulfates of nickel, cobalt and manganese in deionized water, wherein the molar concentration of the total metal in the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at the same time under stirring at 60°C, wherein the concentration of ammonia water is 1.2 mol / L and the concentration of NaOH is 1.0 mol / L; adjusting the pH value to 9.5, stirring is continued at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor: The precursor and lithium hydroxide are mixed in a stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-fired at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. 100g of lithium transition metal oxide, 1.41g of zirconium nitrate, 0.15g of magnesium nitrate, and 0.20g of phosphoric acid are dissolved in an ethanol solution, stirred at high speed for 3 hours, heated and dried at 60°C, fully ground, and calcined at 600°C for 6 hours in an oxygen atmosphere to obtain a positive electrode composite material.
[0141] Preparation of button cells:
[0142] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0143] Embodiment 4:
[0144] Embodiment 4 comprises the following steps:
[0145] Preparation of positive electrode composite materials:
[0146] The positive electrode active material of Example 4 includes Mg 0.5 Zr 2 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The preparation method of the polycrystalline composite material is as follows: dissolving sulfates of nickel, cobalt and manganese in deionized water, wherein the molar concentration of the total metal in the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at the same time under stirring at 60°C, wherein the concentration of ammonia water is 1.2 mol / L and the concentration of NaOH is 1.0 mol / L; adjusting the pH value to 9.5, stirring is continued at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor: The precursor and lithium hydroxide are mixed in a stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-fired at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. 100g of lithium transition metal oxide, 1.78g of zirconium nitrate, 0.19g of magnesium nitrate, and 0.25g of phosphoric acid are dissolved in an ethanol solution, stirred at high speed for 3 hours, heated and dried at 60°C, fully ground, and calcined at 600°C for 6 hours in an oxygen atmosphere to obtain a positive electrode composite material.
[0147] Preparation of button cells:
[0148] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in a N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0149] Embodiment 5:
[0150] Embodiment 5 comprises the following steps:
[0151] Preparation of positive electrode composite materials:
[0152] The positive electrode active material of Example 5 includes Mg 0.5 Zr 2 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The preparation method of the polycrystalline composite material is as follows: dissolving sulfates of nickel, cobalt and manganese in deionized water, wherein the molar concentration of the total metal in the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at the same time under stirring at 60°C, wherein the concentration of ammonia water is 1.2 mol / L and the concentration of NaOH is 1.0 mol / L; adjusting the pH value to 9.5, stirring is continued at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor: The precursor and lithium hydroxide are mixed in a stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-fired at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. 100g of lithium transition metal oxide, 2.17g of zirconium nitrate, 0.24g of magnesium nitrate, and 0.29g of phosphoric acid are dissolved in an ethanol solution, stirred at high speed for 3 hours, heated and dried at 60°C, fully ground, and calcined at 600°C for 6 hours in an oxygen atmosphere to obtain a positive electrode active material.
[0153] Preparation of button cells:
[0154] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0155] Embodiment 6:
[0156] Embodiment 6 comprises the following steps:
[0157] Preparation of positive electrode composite materials:
[0158] The positive electrode active material of Example 6 includes a 5 nm thick Ca 0.5 Zr 2 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The preparation method of the polycrystalline composite material is as follows: dissolving nickel, cobalt and manganese nitrates in deionized water, wherein the total metal molar concentration of the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at the same time under stirring at 60°C, wherein the ammonia concentration is 0.9 mol / L and the NaOH concentration is 2.0 mol / L; adjusting the pH value to 9.5, stirring is continued at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 160°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor: The precursor and lithium hydroxide are mixed in a stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-calcined at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. 100g of lithium transition metal oxide, 1.35g of zirconium nitrate, 0.18g of calcium nitrate, and 0.21g of phosphoric acid are dissolved in an ethanol solution, stirred at high speed for 3 hours, heated and dried at 60°C, fully ground, and calcined at 575°C for 8 hours in an oxygen atmosphere to obtain a positive electrode composite material.
[0159] Preparation of button cells:
[0160] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0161] Embodiment 7:
[0162] Embodiment 7 comprises the following steps:
[0163] Preparation of positive electrode composite materials:
[0164] The positive electrode active material of Example 7 includes Mg 0.5 Zr 2 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The single crystal composite material is prepared by the following method: dissolving nickel, cobalt and manganese nitrates in deionized water, wherein the total metal molar concentration of the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at 60°C under stirring conditions, wherein the ammonia concentration is 0.9 mol / L and the NaOH concentration is 2.0 mol / L; adjusting the pH value to 9.5, continuing stirring at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor: The precursor and lithium hydroxide are mixed in a stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-fired at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. The lithium transition metal oxide is mixed and crushed by high-energy ball milling, and calcined at 700°C for 8 hours in an oxygen atmosphere to obtain an uncoated lithium transition metal oxide single crystal material. 100g of lithium transition metal oxide single crystal material, 1.41g of zirconium nitrate, 0.15g of magnesium nitrate, and 0.20g of phosphoric acid are dissolved in an ethanol solution, fully stirred at high speed for 3 hours, heated and dried at 60°C, fully ground, and calcined at 600°C for 6 hours in an oxygen atmosphere to obtain a positive electrode composite material.
[0165] Preparation of button cells:
[0166] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0167] Comparative Example 1:
[0168] Comparative Example 1 comprises the following steps:
[0169] Preparation of Lithium Transition Metal Oxide Polycrystalline Materials:
[0170] Nitrate of nickel, cobalt and manganese was dissolved in deionized water, wherein the total molar concentration of metal in the obtained solution was 2 mol / L, and ammonia water and NaOH alkaline solution were added simultaneously under stirring at 60°C, wherein the concentration of ammonia water was 0.9 mol / L and the concentration of NaOH was 2.0 mol / L, and the pH value was adjusted to 9.5, and stirring was continued at this pH for 4 hours, and the obtained solution was washed with water, filtered, and dried in an oven at 160°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor, the precursor and lithium hydroxide are mixed according to the stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-fired at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in an oxygen atmosphere to obtain an uncoated lithium transition metal oxide material LiNi 0.92 Co 0.04 Mn 0.04 O 2 .
[0171] Preparation of button cells:
[0172] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2, dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0173] Comparative Example 2:
[0174] Comparative Example 2 comprises the following steps:
[0175] Preparation of lithium transition metal oxide single crystal materials:
[0176] The sulfates of nickel, cobalt and manganese were dissolved in deionized water, wherein the molar concentration of the total metal in the obtained solution was 3 mol / L, and ammonia water and NaOH alkaline solution were added simultaneously under stirring at 60°C, wherein the concentration of ammonia water was 1.2 mol / L and the concentration of NaOH was 1.0 mol / L, and the pH value was adjusted to 9.5, and stirring was continued at this pH for 4 hours, and the obtained solution was washed with water, filtered, and dried in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor, the precursor and lithium hydroxide are mixed according to the stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-fired at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in an oxygen atmosphere to obtain lithium transition metal oxide LiNi 0.92 Co 0.04 Mn 0.04 O 2 The lithium transition metal oxide is mixed and crushed by high-energy ball milling, and calcined at 700°C for 8 hours in an oxygen atmosphere to obtain an uncoated single crystal material.
[0177] Preparation of button cells:
[0178] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0179] Comparative Example 3:
[0180] Comparative Example 3 comprises the following steps:
[0181] Preparation of Lithium Transition Metal Oxide Polycrystalline Materials:
[0182] The positive electrode active material of Comparative Example 3 includes a 5 nm thick Zr 2.25 (PO 4 ) 3 LiNi coating 0.92 Co 0.04 Mn 0.04 O 2 The preparation method of the polycrystalline composite material is as follows: dissolving sulfates of nickel, cobalt and manganese in deionized water, wherein the molar concentration of the total metal in the obtained solution is 3 mol / L, then adding ammonia water and NaOH alkaline solution at the same time under stirring at 60°C, wherein the concentration of ammonia water is 1.2 mol / L and the concentration of NaOH is 1.0 mol / L; adjusting the pH value to 9.5, stirring is continued at this pH for 4 hours, washing and filtering the obtained solution reactant with water, and drying in an oven at 150°C for 3 hours to obtain Ni 0.92 Co 0.04 Mn 0.04 (OH) 2 Precursor: The precursor and lithium hydroxide are mixed in a stoichiometric ratio of 1:1.02, and then transferred to a tube furnace, pre-calcined at 475°C for 3 hours in an oxygen atmosphere, and then calcined at 745°C for 12 hours in oxygen to obtain a lithium transition metal oxide. 100g of lithium transition metal oxide, 1.49g of zirconium nitrate, and 0.20g of phosphoric acid are dissolved in an ethanol solution, stirred at high speed for 3 hours, heated and dried at 60°C, fully ground, and calcined at 600°C for 6 hours in an oxygen atmosphere to obtain a positive electrode composite material.
[0183] Electrochemical testing:
[0184] The button cells of Examples 1-7 and Comparative Examples 1-3 were subjected to electrochemical tests to test their reversible discharge capacity at 0.1C, first cycle coulombic efficiency, and 100 cycle capacity retention rate. The obtained data are shown in Table 1.
[0185] [Table 1]
[0186]
[0187]
[0188] It can be seen that compared with Comparative Examples 1-3, Examples 1-7 exhibit excellent cycle performance, for example, Figure 3As shown, the first-cycle coulombic efficiency of Example 3 reaches 91.7%, indicating that it can significantly inhibit the side reaction between the electrolyte and the lithium transition metal oxide positive electrode material and increase the diffusion rate of lithium ions, thereby significantly improving the structural stability of the lithium transition metal oxide positive electrode material and the slow lithium ion transfer kinetics.
[0189] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present disclosure, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises a lithium transition metal oxide having the following chemical formula 1 and a coating layer coated on the surface of the lithium transition metal oxide; Chemical formula 1: LiNi a Co b Mn c M 1 d O2 Where a+b+c+d=1, 0.80≤a≤1, 0≤b≤0.20, 0≤c≤0.20, 0≤d≤0.10, M 1 At least one selected from Al, B, Sr, Y, Ba, W, Ca, Cu, Fe, V, Cr, Ti, Zr, Zn, In, Ta, La, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo; the coating layer comprises a phosphate material, the phosphate material having M 0.5 The chemical formula of Zr2(PO4)3, M is selected from at least one of Mg, Ca, Ni and Mn.
2. The positive electrode active material according to claim 1, characterized in that The phosphate material has a NASICON structure.
3. The positive electrode active material according to claim 1, characterized in that The coating layer has a thickness of 2-10 nm.
4. The positive electrode active material according to claim 1, characterized in that The positive electrode active material comprises primary particles with a Dv50 of 2-5 μm; and / or Secondary particles with a Dv50 of 10-14 μm.
5. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the positive electrode active material, the mass percentage of the phosphate material is 0.3-1.2%.
6. The positive electrode active material according to claim 1, characterized in that The phosphate material is selected from Mg 0.5 Zr2(PO4)3 and / or Ca 0.5 Zr2(PO4)3.
7. A method for preparing the positive electrode active material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: Dissolving the lithium transition metal oxide, zirconium salt, phosphoric acid and metal salt of M in a solvent; Stirring for 2-6 hours, and drying to obtain a mixture; The mixture is subjected to a heating treatment to obtain a positive electrode active material.
8. The method according to claim 7, wherein: The method satisfies at least one of the following conditions: (i) the molar ratio of the lithium transition metal oxide, zirconium salt, phosphoric acid and metal salt of M is selected from (1): (0.002-0.01): (0.002-0.015): (0.001-0.005); (ii) the metal salt of M is selected from at least one of magnesium nitrate, calcium nitrate, nickel nitrate and manganese nitrate; (iii) the solvent comprises ethanol; (iv) the heating treatment is carried out in an oxygen atmosphere; (v) The temperature of the heating treatment is selected from 500°C to 700°C.
9. An electrochemical device, characterized in that: The electrochemical device comprises the positive electrode active material according to any one of claims 1 to 6.
10. An electrical device, characterized in that: The electrical device comprises the electrochemical device according to claim 9.